Challenging suboptimal infection control - Cioffi, Domenico; Cioffi, Jane (International Journal of Infection Control, 2015)
Healthcare associated infections are the most commonly reported complications affecting patients in the global healthcare environment. The rate is increasing. A substantial proportion is attributable to the suboptimal infection prevention and control practice of healthcare workers. This paper discusses the current status of healthcare associated infections, the strategies used to date to improve suboptimal practice, and applies the social psychology paradigm to provide insight into resistance to changing suboptimal practice.